The Operational, Economic and Environmental Benefits of Returnable Packaging Under Various Reverse Logistics Arrangements - Nophanut Katephap; Sunpasit Limnararat (My University, 2017)
This research investigates the operational, economic and environmental advantages of the returnable packaging under various reverse logistics arrangements, in relation to the disposable packaging.The business under study is a Thai manufacturer and exporter of automotive parts with the trading partners in the Philippines and Vietnam.In the study, a switch was made from the currently disposable packaging to the standardized returnable packaging under three reverse logistics arrangements: the single-, round-and multi-trip arrangements.Due to the large initial investment associated with the returnable packaging, a mathematical model was proposed to calculate the total effective packaging cost.The research findings revealed that the multi-trip reverse logistics arrangement was most operationally and environmentally viable, with the largest total packaging cost reduction and packaging waste reduction of 61% and 68%, relative to the disposable packaging.Meanwhile, the single-trip reverse logistics arrangement was most favorable economically due to its shortest payback period of 0.33 year.Moreover, the life cycle assessment (LCA) was applied to the disposable and returnable packaging to evaluate the environmental impacts throughout their lifetime.The LCA results validate the more environmentally-friendly nature of the returnable packaging.
Keywords: Reverse Logistics; Investment; Environmentally Friendly; Operational costs; Sustainable Supply Chain Management